The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/nau.24195
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and safety of GreenLight photovaporization of the prostate in the high‐risk patient with lower urinary tract symptoms due to benign prostatic enlargement

Abstract: Aims: Photovaporization of the prostate (PVP) with GreenLight Laser is a surgical treatment for lower urinary tract symptoms. It is considered safe in elderly patients with comorbidities, however, the evidence is inconclusive. The objective of this study is to evaluate the efficacy and safety outcomes of PVP according to the American Society of Anesthesiologists Physical Status (ASAPS). Methods: A cohort of 675 patients who underwent PVP between 2012 and 2018 was evaluated. Patients were classified according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Lower urinary tract symptoms (LUTS) measured by IPSS in the high‐risk group significantly improved at a similar rate in low‐risk patients. Barco‐Castillo et al., 11 however, found that patients with higher ASA scores had less improvement than the lower score group. There was no difference in groups that had IPSS improvement.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Lower urinary tract symptoms (LUTS) measured by IPSS in the high‐risk group significantly improved at a similar rate in low‐risk patients. Barco‐Castillo et al., 11 however, found that patients with higher ASA scores had less improvement than the lower score group. There was no difference in groups that had IPSS improvement.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the benign prostatic hyperplasia (BPH) prevalence in the aging population, there has been an increase in age and medical comorbidities in patients requiring BPH surgery 8 . Multiple studies have attempted to use these risk stratification to predict outcomes from surgery 9–11 . Additionally, there has been increased interest in newer technologies that do not require general anesthesia in those who are felt to be unfit for anesthesia, such as transurethral bipolar radiofrequency thermotherapy (Bipolar‐RF) and water vapor thermal therapy (WVTT) 12,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPH is the most common disease in elderly men. When the disease progresses to a certain stage, patients often suffer from chronic urinary retention due to obstruction of lower urinary tract, causing lower abdominal pain, repeated urinary tract infection, hematuria, which easily lead to serious coplications such as bladder dysfunction, renal insufficiency, electrolyte disturbance, etc., and poses a serious threat to the health of elderly men ( 11 13 ). Although BPH high-risk patients have obvious symptoms of lower urinary tract obstruction and their quality of life declines, their tolerance to anesthesia and surgical intervention is poor due to physical factors.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk patients with BPH are often accompanied by basic diseases such as hypertension and diabetes. In addition, they are elderly and have poor body resistance, which greatly increases the difficulty of treatment ( 3 , 4 ). At present, surgical treatment is commonly used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%